Requirements demanded of accounting practitioners by the market in the second half of the 19th century - Vasconcelos, Angélica; Silva, Adriana; Gomes, Patrik; Vieira, Cilene (Revista Contabilidade & Finanças, 2023)
This study aims to identify the requirements demanded of accounting practitioners by the market in the second half of the 19th century in the state of Pará. Standing out from the existing literature, this study broadens the understanding of the history of the accounting profession as an occupation, through the use of concepts derived from the sociological theory of professions. The relevance of the topic chosen lies in understanding the impact of the requirements demanded of accounting practitioners on the professionalization process and on the modeling of the limits of the occupational structure. The evidence provides the possibility of strengthening the research in the area of accounting history by demonstrating the difficulty of defining what an “accounting practitioner” was, since the expression covered an infinity of employment situations, the performance of various tasks, and included specialized sub-occupations. The study involves archival research, based on job advertisements published in newspapers that circulated in Pará in the period from 1859 to 1888, available from the National Library of Brazil. The requirements analyzed were demographic characteristics (sex, age, nationality, and marital status) and competences. The findings were compared with those of similar studies, as well as with studies that analyze a contemporary period. The results of this research indicate that the market required accounting practitioners to be male, between 12 and 16 years old, with good conduct confirmed by a reference provider, and practical knowledge that was not always restricted to the accounting universe. The findings demonstrate that there was no objective definition of the limits of the identity of the occupation and, in essence, the requirements demanded of accounting practitioners in the second half of the 19th century persist over time. The contribution of this research consists of broadening and deepening the historical understanding of the nature of the accounting occupation in Pará, an area of less commercial prominence during the second half of the 19th century.